Literature Study: Effectiveness of Benson Relaxation on Anxiety in Hemodialysis Patients - Aprilia Kartika Sari; Dian Hudiyawati (Journal of Nursing Science Update (JNSU), 2021)
Chronic kidney disease (CKD) is a disease of kidney function disorders that occurs when the body fails to maintain metabolism, fluid, and electrolyte balance which can cause retention of urea and nitrogen waste in the blood. One of the treatments for patients with kidney failure is hemodialysis, but it can also cause psychological issues such as anxiety. Benson relaxation is a nursing intervention that can reduce anxiety. The purpose of this literature is to determine the effectiveness of the Benson relaxation method in reducing anxiety in patients undergoing hemodialysis. The study is a literature review that was conducted using databases such as PubMed, Elsevier, ScienceDirect, Portal Garuda, and Google Scholar, yielding ten articles. The findings indicate that Benson's relaxation therapy is effective in reducing the anxiety level of hemodialysis patients. This exercise will stimulate the brain to release alpha waves that cause humans to feel happy, calm, and feel comfortable. Therefore, Benson relaxation is recommended as an additional intervention for reducing anxiety in hemodialysis patients.